Multimedia literacy in preschool and primary education - Mikelić Preradović, Nives (Array, 2014)
Multimedia literacy represents a set of skills enabling individuals to effectively find, interpret, use, evaluate and even create multimedia. It encompasses abilities needed to process and exploit all components of multimedia: text, sound, image, animation, video and interactivity. According to UNESCO, alphabetic literacy (the ability to identify, understand, interpret, create, communicate, compute and use printed and written materials associated with varying contexts) is a human right and the foundation of all learning. It is also a skill that begins in infancy and continues to grow over the lifetime. But, today’s children are not limited to written materials ; they are frequentconsumers of multimedia, surrounded by video games and dynamic media with a high level of interactivity. They prefer the content presented by graphics, sound and video more than written materials and are impatient for the traditional slow systematic transfer of the learning content. Therefore, they must be taught to construct meaning from multiple modes of presentation of the learning content and to evaluate the multimedia. The first part of the lecture summarizes the necessary elements of multimedia literacy education, its key stakeholders and emphasizes its role in the early years of life. Parents, caregivers and educators all play a role in building the foundation for multimedia literacy. The need for multimedia literacy education puts forward new requirements to caregivers, parents and educators, who are expected to become multimedia literate lifelong learners. On the other hand, preschool and primary school literacy education still tends to focus on alphabetic literacy and traditional approach that does not take into account the wealth of knowledge children acquire through everyday contact with constantly evolving multimedia environments. In the second part of the lecture, a new paradigm implied by multimedia competencies will be discussed. Although they recognize the importance of children to be multimedia literate, a large percentage of preschool and primary school systems in the developed world still does not include multimedia literacy into the obligatory curriculum. If a curriculum combines multiple instructional tools (text, sound, video and images), it is possible to attract children’ attention and deepen their learning experience. Therefore, the last part of the lecture will summarize approaches, similarities, differences, advantages and issues of introducing multimedia literacy education in preschools and primary schools in different countries of the world.